2009
DOI: 10.1038/sj.bjc.6605490
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor signalling and bone metastasis

Abstract: Epidermal growth factor (EGF) signalling is well known for its multifaceted functions in development and tissue homoeostasis. The EGF family of ligands and receptors (ERBB family) have also been extensively investigated for their roles in promoting tumourigenesis and metastasis in a variety of cancer types. Recent findings indicate that EGF signalling is an important mediator of bone metastasis in breast, prostate and kidney cancers. The EGF signalling stimulates the growth of bone metastasis directly by incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 36 publications
2
51
0
Order By: Relevance
“…The poor prognosis and recurrence of HCC are majorly caused by intrahepatic metastasis [2,3]. A lot of evidence demonstrated that growth factors and cytokines such as transforming growth factor (TGFb) [4], platelet derived growth factor [5] epidermal growth factor (EGF) [6], hepatocyte growth factor (HGF) [7] and extracellular matrix (ECM) [8] secreted in the tumor environment may trigger epithelial mesenchymal transition (EMT), migration and invasion of tumor cells [9]. Delineating the molecular pathways mediating these processes may benefit developing effective targeting strategies for prevention of intrahepatic metastasis of HCC.…”
Section: Introductionmentioning
confidence: 99%
“…The poor prognosis and recurrence of HCC are majorly caused by intrahepatic metastasis [2,3]. A lot of evidence demonstrated that growth factors and cytokines such as transforming growth factor (TGFb) [4], platelet derived growth factor [5] epidermal growth factor (EGF) [6], hepatocyte growth factor (HGF) [7] and extracellular matrix (ECM) [8] secreted in the tumor environment may trigger epithelial mesenchymal transition (EMT), migration and invasion of tumor cells [9]. Delineating the molecular pathways mediating these processes may benefit developing effective targeting strategies for prevention of intrahepatic metastasis of HCC.…”
Section: Introductionmentioning
confidence: 99%
“…epidermal growth factor receptor (EGFR; also called ERBB1 or HER1), ERBB2 (also called HER2, ERBB3 or HER3) and ERBB4 (also called HER4) [79][80][81]. Receptors and ligands of ERBB are frequently overexpressed by carcinoma cells [82], with EGFR and ERBB3 overexpressed in 50-70% of lung, colon and breast carcinoma, ERBB2 in 30% of breast cancer patients, and ERBB4 in 50% of breast cancer patients and 22% of colon cancer patients [79].…”
Section: Npc Regulates Egfr Signal Activator Traffic Into the Nucleusmentioning
confidence: 99%
“…Receptors and ligands of ERBB are frequently overexpressed by carcinoma cells [82], with EGFR and ERBB3 overexpressed in 50-70% of lung, colon and breast carcinoma, ERBB2 in 30% of breast cancer patients, and ERBB4 in 50% of breast cancer patients and 22% of colon cancer patients [79].…”
Section: Npc Regulates Egfr Signal Activator Traffic Into the Nucleusmentioning
confidence: 99%
“…The balance between osteoblasts and osteoclasts can be perturbed by altering the activity of EGF signaling as it stimulates growth of bone metastasis directly by increasing tumor cell proliferation and indirectly with bone stromal cell essential for the metastasis development [Lu and Kang, 2010].…”
Section: Egfr Tkismentioning
confidence: 99%